Short-term ambient particulate matter pollution of different sizes and respiratory hospital admission in the Beibu Gulf area of Southern China. (1st February 2023) - Li, Haopeng; Liang, Lizhong; Zhang, Shiyu; Qian, Zhengmin (Min); Cai, Miao; Wang, Xiaojie; McMillin, Stephen Edward; Keith, Amy E.; Wei, Jing; Geng, Yan; Lin, Hualiang
Abstract: Background: Ambient particulate matter (PM) pollution is associated with occurrence of respiratory diseases; however, limited evidence exists on the effects of PM1 due to lack of ground-based PM1 measurements. Objective: To examine the associations of short-term exposure to PM1, PM2.5 and PM10 with respiratory hospital admission, as well as the attributable burden. Methods: A total of 558, 012 respiratory hospital admissions records were collected from 15 cities in the northeast Beibu Gulf of China from 2013 to 2016. Short-term exposures to pollutants (PM1, PM2.5 and PM10 ) were estimated using a bilinear interpolation approach at residential addresses. A time-stratified case-crossover design was constructed to estimate the associations and the burden of respiratory admissions attributable to ambient air pollution. Results: We observed significant associations between PM and respiratory hospitalizations. Odds ratios per 10 μg/m 3 increment in two-day averaged concentration were 1.017 (95% CI: 1.012, 1.021) for PM1, 1.010 (95% CI: 1.007, 1.013) for PM2.5, and 1.007 (95% CI: 1.006, 1.009) for PM10 . Males in the warm season appeared to be more vulnerable to the impacts of ambient PM pollutants. We further estimated that 3.0% (95% CI: 2.7%, 3.2%), 6.5% (95% CI: 5.9%, 6.8%) and 1.8% (95% CI: 1.6%, 1.9%) of respiratory hospital admissions were attributable to short-term exposure of PM1, PM2.5 and PM10, respectively. Conclusions: Short-term exposure to ambient PM might be an important risk factor for respiratory diseases hospital admissions. If environmental PM air pollutants were reduced to current guideline levels set forth by the government, a substantial proportion of respiratory hospitalizations would be mitigated as a result. Highlights: A time-stratified case-crossover design is constructed to estimate the associations. A large-scale, high-quality, and multisite representative dataset is used. Increased risk of respiratory hospitalizations associated with particulate matter. Male in the warm season is more vulnerable to the impacts of particulate pollution. 7% of respiratory hospitalizations is attributable to short-term exposure of PM2.5.